2016
DOI: 10.1186/s41021-016-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of nuclear abnormalities in exfoliated buccal epithelial cells with the health status of different agricultural activities farmers in Peninsular Malaysia

Abstract: BackgroundPesticide exposure possesses risk of genotoxicity to humans, particularly farmers. Despite accumulating evidences linking genotoxicity to pesticide exposure, epidemiological studies to address pesticide toxicity in occupationally exposed farmers in Malaysia remain underreported. Thus, this study was aimed to determine the presence of nuclear abnormalities through the assessment of micronucleus (MN) and binucleus (BNu) frequencies in exfoliated buccal epithelial cells from farmers who were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…Contrary to this, other studies have reported an increment in DNA injury induced by exposure to pesticides [ 2 , 21 , 22 , 26 , 27 , 28 ]. In these cases, a low awareness of pesticide risk has been assumed [ 29 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Contrary to this, other studies have reported an increment in DNA injury induced by exposure to pesticides [ 2 , 21 , 22 , 26 , 27 , 28 ]. In these cases, a low awareness of pesticide risk has been assumed [ 29 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Benedetti et al [ 48 ] found significant increases in the frequency of MN in soybean workers. Analysis of buccal cells in a group of Malaysian farmers revealed that the frequency of MN was significantly higher in pesticide-exposed farmers as compared to controls (office workers) [ 49 ]. Similarly to our outcome, da Silva et al [ 50 ] reported DNA damage in tobacco workers associated with the exposure to herbicides (organophosphates) and insecticides (carbamates).…”
Section: Discussionmentioning
confidence: 99%
“…But if the selling of straw replaces on a large scale, for example, mulching or incorporation, then this can have negative effects on the soil and indirectly on human health. If more chemicals, such as fertiliser are needed, this can lead to health risks (Abdul et al, 2016; Nganchamung et al, 2017). Our respondents indicated suffering many mental and physical challenges due to spraying chemicals already.…”
Section: Discussionmentioning
confidence: 99%